Climate change and coconut plantations in India: Impacts and potential adaptation gains - S. Naresh Kumar and, P.K. Aggarwal
The assessment of impact of climate change on coconut, a plantation crop, is challenging. However, the development of a simulation model (InfoCrop-COCONUT) has enabled the process. We present the first simulation analysis of the potential impacts of climate change on coconut productivity in India following two approaches, namely: (i) ‘fixed increase in temperature and CO 2 , and (ii) scenarios as per PRECIS (Pro- viding Regional Climates for Impact Studies) – a regional climate model. Impact of changed management on coconut productivity in current as well as in future climates is also assessed. Climate change is pro- jected to increase coconut productivity in western coastal region, Kerala, parts of Tamil Nadu, Karnataka and Maharashtra (provided current level of water and management is made available in future climates as well) and also in North-Eastern states, islands of Andaman and Nicobar and Lakshadweep while neg- ative impacts are projected for Andhra Pradesh, Orissa, West Bengal, Gujarat and parts of Karnataka and Tamil Nadu. On all India basis, even with current management, climate change is projected to increase coconut productivity by 4.3% in A1B 2030, 1.9% in A1B 2080, 6.8% in A2 2080 and 5.7% in B2 2080 sce- narios of PRECIS over mean productivity of 2000–2005 period. Agronomic adaptations like soil moisture conservation, summer irrigation, drip irrigation, and fertilizer application cannot only minimize losses in majority of coconut growing regions, but also improve productivity substantially. Further, genetic adap- tation measures like growing improved local Tall cultivars and hybrids under improved crop manage- ment is needed for long-term adaptation of plantation to climate change, particularly in regions that are projected to be negatively impacted by climate change. Such strategy can increase the productivity by about 33% in 2030, and by 25–32% in 2080 climate scenarios. In fact, productivity can be improved by 20% to almost double if all plantations in India are provided with above mentioned management even in current climates. In places where positive impacts are projected, current poor management may become a limiting factor in reaping the benefits of CO 2 fertilization, while in negatively affected regions adaptation strategies can reduce the impacts. Thus, intensive genetic and agronomic adaptation to cli- mate change can substantially benefit the coconut production in India.